THE ROLE OF SELF-STUDY IN LEARNING A FOREIGN LANGUAGE - Gafurova Nozima Ikramovna; Karimova Kamola Rustam qizi; Obidova Shoxistaxon Nuridinjon qizi (Journal of Innovation in Education and Social Research, 2023)
This article presents a comprehensive examination of the significance of self-study in learning a foreign language and in what ways it can be effective for students. The paper aims to identify the benefits of self-study and suggests some tips while doing self-study in learning foreign languages. By analyzing relevant literature, case studies, and expert recommendations, this research aims to contribute to the field of doing self-study in learning a foreign language.